Aktivitas antioksidan yoghurt susu biji ketapang (Terminalia catappa L.) dengan penambahan ekstrak daun seledri (Apium graveolens L.) - Nanik Suhartatik; Merkuria Karyantina; Kharis Triyono; Yudha Dwi Haryo Bintoro (AGROINTEK, 2023)
Tropical almonds (Terminalia catappa L) are food ingredients that can be developed into probiotic drinks like yogurt. The addition of celery leaf extract in to yoghurt can affect the growth of the bacteria. Celery leaf contain natural antimicrobial compounds that can influence bacterial growth. However, celery also contain bioactive compounds that can improve the functional properties of food.  This study aimed to determine the antioxidant activity of tropical almond yogurt with the addition of celery leaves. The research method used was factorial Completely Randomized Design (CRD), with the first factor being the type of starter culture and the second factor the fermentation time (0, 2, 4, 6, 8, 12, and 16h). The starter culture included Lactobacillus bulgaricus (Lb), Streptococcus thermophilus (St), and Lactobacillus bulgaricus - Streptococcus thermophilus (St-Lb). Data analysis used Duncan Multiple Range Test with a significance level of 5%. The results showed that after 16h of fermentation, the total acid-producing bacteria was at 7.47 log CFU/ml. This value met the standard criteria for probiotics products. Antioxidant activity with the highest percentage of inhibition (97.11%) was found in yogurt with a starter type of St-Lb. This product had 7.21 log CFU/ml of total acid-producing bacteria, total phenol content (TPC) of 143.61 mg GAE/ 100 ml, total flavonoids of 281.22 mg QE/g, a total sugar content of 25.76%, and protein content of 13.38%. Tropical almond yoghurt, with the addition of celery leaves, has the potential to be developed as a functional food. Further research need to investigate the functional properties of the yoghurt.